2002
DOI: 10.1007/s002850200151
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary suicide and evolution of dispersal in structured metapopulations

Abstract: We study the evolution of dispersal in a structured metapopulation model. The metapopulation consists of a large (infinite) number of local populations living in patches of habitable environment. Dispersal between patches is modelled by a disperser pool and individuals in transit between patches are exposed to a risk of mortality. Occasionally, local catastrophes eradicate a local population: all individuals in the affected patch die, yet the patch remains habitable. We prove that, in the absence of catastroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
177
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 138 publications
(181 citation statements)
references
References 47 publications
2
177
2
Order By: Relevance
“…If the resultant densities fall below the threshold density of an allee effect, or if they imply a much elevated risk of accidental extinction, the population is doomed. The potential ubiquity of selection-driven extinctions is underscored by other examples of extinctions caused by adaptation in different traits, including anti-predator behavior (Matsuda and Abrams, 1994b), sexual traits (Kirkpatrick, 1996;Kokko and Brooks, 2003), dispersal rates (Gyllenberg et al, 2002), mutualism rates , cannibalistic traits , maturation reaction norms (Ernande et al, 2002), levels of altruism (Le Galliard et al, 2003), and selfing rates (Cheptou, 2004); see also the review by Parvinen (2006). Furthermore, Dieckmann and Ferrie`re (2004) showed, by examining ecologically explicit multilocus models featuring either diallelic loci or continua of alleles, that the incidence of evolutionary suicide is by no means restricted to phenotypic models of asexual evolution, but robustly occurs also when sexual inheritance is taken into account.…”
Section: Article In Pressmentioning
confidence: 99%
“…If the resultant densities fall below the threshold density of an allee effect, or if they imply a much elevated risk of accidental extinction, the population is doomed. The potential ubiquity of selection-driven extinctions is underscored by other examples of extinctions caused by adaptation in different traits, including anti-predator behavior (Matsuda and Abrams, 1994b), sexual traits (Kirkpatrick, 1996;Kokko and Brooks, 2003), dispersal rates (Gyllenberg et al, 2002), mutualism rates , cannibalistic traits , maturation reaction norms (Ernande et al, 2002), levels of altruism (Le Galliard et al, 2003), and selfing rates (Cheptou, 2004); see also the review by Parvinen (2006). Furthermore, Dieckmann and Ferrie`re (2004) showed, by examining ecologically explicit multilocus models featuring either diallelic loci or continua of alleles, that the incidence of evolutionary suicide is by no means restricted to phenotypic models of asexual evolution, but robustly occurs also when sexual inheritance is taken into account.…”
Section: Article In Pressmentioning
confidence: 99%
“…At equilibrium, this quantity should equal 1, hence R I . It can also be shown that the equilibrium value of R I given by Equation (5b) tends to R 0 as the immigration rate I tends to zero (Gyllenberg et al 2002).…”
Section: Defining Basic Reproduction Ratiosmentioning
confidence: 96%
“…To investigate this question we have to turn to more complicated models that explicitly prescribe local dynamics in terms of parameters that describe individual behavior. Such models are called structured metapopulation models and have been treated by, among others, Gyllenberg andHanski (1992, 1997), Hanski and Gyllenberg (1993), Gyllenberg et al ( , 2002, Gyllenberg and Metz (2001), Metz and Gyllenberg (2001), and Parvinen (2001a, 2001b. In Section 4 the persistence and viability of metapopulations is investigated within the context of structured models.…”
Section: Persistence and Viabilitymentioning
confidence: 99%
See 2 more Smart Citations